¿Alegoría, retrato, manifiesto? Una revisión de las lecturas hechas a “La Pittura”, de Artemisia Gentileschi - Huanca Lara, Grecia (Pontificia Universidad Católica del Perú, 2025)
The article examines the main interpretive trends that have emerged around Artemisia Gentileschi’s La Pittura. It argues that interpretations of this painting have been shaped by two main approaches: one that highlights the artist’s exceptionality and agency, and another that proposes a critical decentralization of that very exceptionality. Through the analysis of these perspectives, the study contends that the painting has become a fertile ground for debate on self-representation, gender, and female agency in Baroque art.

El artículo propone una revisión historiográfica de las interpretaciones que han surgido sobre la obra “La Pittura”, de Artemisia Gentileschi. Se argumenta que las lecturas sobre esta pintura han estado marcadas por dos enfoques principales: uno que resalta la excepcionalidad y agencia de la artista y otro que propone una descentralización crítica de dicha excepcionalidad. A partir del análisis de estas perspectivas, se argumenta que la obra se ha convertido en un terreno fértil para debatir sobre autorrepresentación, género y agencia femenina en el arte barroco.
Allegory, portrait, manifesto? A review of interpretations of Artemisia Gentileschi’s “La Pittura”
Keywords: Artemisia Gentileschi; “La Pittura”; Self-portrait; Baroque art; Gender studies; Artemisia Gentileschi; “La Pittura”; Autorretrato; Arte barroco; Estudios de género; https://purl.org/pe-repo/ocde/ford#5.04.03